Improving Mathematics Learning Outcomes of Class XII-2 MAN Kajuara Through the Example Non Example Learning Model - Suhaeni,; Irwan, Anas; Amin, Badaruddin (Alauddin Journal of Mathematics Education, 2023)
The purpose of this study was to determine the increase in students' mathematics learning outcomes through the application of the Example Non Example learning model. The research method used was classroom action research on 31 students in class XII-2 of MAN Kajuara, Bone Regency. The instruments used are learning achievement tests and observation sheets of student learning activities. Descriptive analysis is a data analysis technique used in this study. The results of the data analysis showed that the results of students' mathematics learning with the Example Non Example learning model experienced an increase in each cycle. In the first cycle the completeness of student learning outcomes reached 64,5% and experienced an increase in the second cycle of 87,1%. Thus, it can be concluded that the Example Non Example learning model is able to improve students' mathematics learning outcomes.